A controlled study of the efficacy and safety of tandospirone citrate combined with escitalopram in the treatment of vascular depression: A pilot randomized controlled trial at a single-center in China. (July 2019) - Chen, Hongbin; Lin, Qianwen; Lin, Ting; Lin, Yongsen; Lin, Xiaohui; Chen, Ronghua; Luo, Ling; Lin, Feifei; Xiao, Yingchun
Abstract: Vascular depression can respond poorly to antidepressants. This study aimed to explore the efficacy and safety of tandospirone plus escitalopram for treating vascular depression with anxiety. This pilot randomized controlled trial included consecutive inpatients/outpatients with vascular depression/anxiety at the Department of Neurology, Fujian Medical University Union Hospital, China (January 2014 to December 2016). Among 157 patients screened, 100 were randomly divided into the tandospirone + escitalopram (combination therapy) and escitalopram (monotherapy) groups equally, and then followed for 8 weeks. Efficacy was evaluated using the Hamilton Depression (HAMD), Hamilton Anxiety (HAMA), Clinical Global Impression (CGI) and Mini-Mental State examination (MMSE) scales. Adverse events (AEs) were assessed with the Treatment Emergent Symptom Scale (TESS). HAMD and HAMA scores decreased progressively, showing reductions versus baseline at 1, 2, 4 and 8 weeks in both groups ( P  < 0.001). HAMD and HAMA scores were lower in the tandospirone + escitalopram group than those in the escitalopram group at 1 and 2 weeks ( P  < 0.001), but not at 4 and 8 weeks. Improvements in CGI scores (severity, improvement and efficacy indexes) were greater in the tandospirone + escitalopram group than that in the escitalopram group at 1 and 2 weeks ( P  < 0.01), but not at 4 and 8 weeks. The tandospirone + escitalopram group had higher MMSE scores than that in the escitalopram group at 4 and 8 weeks ( P  < 0.01). All AEs were mild, and the rates were comparable between groups. Augmentation of escitalopram with tandospirone accelerates the onset of anti-depressive and anxiolytic effects and improves cognitive function in patients with vascular depression and anxiety.